Case Report: Insulinoma Co-Existing With Type 2 Diabetes – Advantages and Challenges of Treatment With Endoscopic Ultrasound-Guided Radiofrequency Ablation - Chang, Johnny Yau-Cheung; Woo, Chariene Shao-Lin; Lui, David Tak-Wai; Fung, Matrix Man-Him; Lee, Alan Chun-Hong; Leung, Eunice Ka-Hong; Woo, Yu-Cho; Chow, Wing-Sun; Lam, Karen Siu-Ling; Tan, Kathryn Choon-Beng; Lee, Chi-Ho (Frontiers in Endocrinology, 2022)
The coexistence of insulinoma and type 2 diabetes is rare and the diagnostic process is often challenging. Continuous glucose monitoring system devices, which are more readily available nowadays, provide a useful tool for the diagnosis and evaluation of treatment response. Curative surgery is often the mainstay of treatment for insulinoma. Here, we report a Chinese patient with insulinoma diagnosed simultaneously with type 2 diabetes. His insulinoma was managed with endoscopic ultrasound guided-radiofrequency ablation (EUS-RFA) and the patient achieved complete resolution of hypoglycaemic episodes. The case illustrates that while EUS-RFA is an emerging non-invasive treatment modality for pancreatic lesions, limitations exist especially when histological confirmation is essential.